P.196 Antiplatelet, anticoagulant, or endovascular treatment for stroke prevention in blunt cerebrovascular injury: Retrospective review, systematic review and meta-analysis. (November 2021) - Ku, JC; Priola, SM; Taslimi, S; Mathieu, F; Pasarikovski, CR; Kumar, A; Machnowska, M; Nathens, A; Yang, V; da Costa, L
Abstract : Background: Ischemic stroke occurs following trauma-related blunt cerebrovascular injury (BCVI) in up to 20% of cases. Preventative treatment includes antiplatelets, anticoagulants, and/or endovascular treatment (ET), but the optimal choice remains unclear. The objective of this study was to compare the ischemic stroke rate between these three treatments. Methods: Following PRISMA guidelines, we queried the OVID Medline, Embase, Web of Science, and Cochrane Library databases from September 2019 to inception to identify studies reporting treatment-stratified outcomes in BCVI patients. Meta-analysis was performed to compare outcomes between the treatment groups, using odds ratios. Retrospective review of our institutional experience with BCVI outcomes was performed and added to the meta-analysis. Results: Analysis of seven comparative studies of antiplatelets (n=334) versus anticoagulation (n=325) found no significant difference in ischemic stroke rate (OR 1.27, 95%CI 0.40-3.99), but a decrease in hemorrhagic complications (OR 0.38, 95%CI 0.15-1.00). Analysis of seven comparative studies of antiplatelets/anticoagulants (n=805) versus ET (n=235) also found no significant difference in stroke rate (OR 0.71, 95%CI 0.35-1.42). Conclusions: Antiplatelets and anticoagulants were similarly effective in reducing ischemic stroke risk in BCVI, but antiplatelets were better tolerated in this trauma population. The addition of endovascular treatment did not further reduce stroke risk compared to antiplatelets or anticoagulants alone.